Предмет: Алгебра,
автор: Аноним
Разложите на множители
1)x(a-b)+y(b-a)
2)m²(a-2)+n(2-a)
Ответы
Автор ответа:
0
1)x(a-b)+y(b-a)=x(a-b)-y(a-b)=(x-y)(a-b)
2)m²(a-2)+n(2-a)=m²(a-2)-n(a-2)=(m²-n)(a-2)
2)m²(a-2)+n(2-a)=m²(a-2)-n(a-2)=(m²-n)(a-2)
Автор ответа:
0
1)x(a-b)+y(b-a)=x(a-b)+y(-1)(a-b)=x(a-b)-y(a-b)=(x-y)(a-b)
2)m²(a-2)+n(2-a)=m²(a-2)+n(-1)(a-2)=m²(a-2)-n(a-2)=(m²-n)(a-2)
2)m²(a-2)+n(2-a)=m²(a-2)+n(-1)(a-2)=m²(a-2)-n(a-2)=(m²-n)(a-2)
Похожие вопросы
Предмет: Английский язык,
автор: rektut2016
Предмет: Русский язык,
автор: kenmacrash3456
Предмет: Русский язык,
автор: Kenati
Предмет: Математика,
автор: valeriyalisits2
Предмет: Алгебра,
автор: assema1998